The desire of power: Candidate ambiguity and incumbent monopoly in local leaders’ election - Erond L. Damanik (Faculty of Social and Political Science, Universitas Airlangga, 2020)
This study explores and discusses the phenomenon of a single candidate in the local leaders’ election or Pemilihan Kepala Daerah (Pilkada) in Deli Serdang Regency, North Sumatra Province, in 2018. The study is motivated by the phenomenon of a single candidate in the local leaders’ election. In Deli Serdang, the local leaders’ election should have a multi-candidate pattern, either independent or 3-4 political party candidates. This study has focused on the mechanism of the emergence of a single candidate. According to Dahl, the theoretical approach is the candidacy mechanism, and according to Norris, the significance of the right to vote. The study was conducted qualitatively with an ongoing explorative, independent, and case-oriented study approach. The data collected through in-depth interviews with nine key informants consisting of the Political Party Branch Management Board or Dewan Pimpinan Cabang (DPC), the General Elections Commission or Komisi Pemilihan Umum (KPU), the Election Supervisory Committee or Panitia Pengawas Pemilihan (Panwaslih), independent, failed, and incumbent candidates. The sixteen secondary informants consisted of eight voting behaviors and eight non-voting behaviors randomly selected and interviewed to determine their perception of a single candidate. The study found that a single candidate is the logical consequence of ambiguity in an internal political party candidacy. The study’s novelty is the exclusion of incumbent ruling candidates incentivizing a political party monopoly to ensure victory in contestation. The study concluded that the dysfunction of the candidacy and exclusion in power has implications for a single candidate in the local leaders’ election. Contestation with a single candidate’s presence is an uncontested election, and it is contrary to the theoretical paradigm referred to in this study.